PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP TANGGUNG JAWAB DOKTER JAGA DI INSTALASI GAWAT DARURAT BERDASARKAN HUKUM POSITIF INDONESIA - Rudianto Rudianto Rudianto (Jurnal Idea Hukum, 2018)
Service at IGD many find difficult, such as the State of the patient is not conscious and there is no family that takes, so the doctor IGD should get legal protection in the conduct of medical action. The problem occurs because the doctor IGD in conditions like this should serve patients in the shortest – in short with the doctor in the service of the response time of the IGD is less than 5 (five) minutes, in order to save lives and more disability prevention further, while the doctor IGD that is in the RS are currently limited in number.The purpose of research to analyse the implementation of the responsibility of the doctor in dealing with patients at IGD hospital. This type of research is descriptive, the juridical sociological approach is the method. The primary data source as the primary data collected from the field, and secondary data as supporting data. The data obtained were analyzed using qualitative methods, with the constant comparison analysis models and techniques of analysis done with the method of Theoretical Interpretation.Aspects of the implementation of the responsibility of the doctor IGD-positive, however there are doctor IGD substitute that does not have SIP for lack of doctor IGD especially when holiday Lebaran. Doctor who practise without having a SIP don't get legal protection, from the beginning of the Administration had broken the law and may be subject to disciplinary action from the City/County Health Department in addition to criminal sanctions as set forth in Article 76 of ACT No. 29 of the year 2004 about the practice of medicine